The Effect of Central Government Assistance, Programme Implementation Quality, and Financial Behaviour on the Welfare of Beneficiary Families in Sambas Regency - An Am Alhamzi; Erni Panca Kurniasih (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study aims to analyze the effect of Central Government Assistance, program implementation quality, and financial behavior on the welfare of beneficiary families in Sambas Regency. The research method used is a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The population of the study includes all BPP recipient families in Sambas Regency, with samples taken using two-stage cluster sampling. Primary data were collected through Likert-scale questionnaires, and secondary data were obtained from the Sambas Social Service. The analysis results show that Central Government Assistance, program implementation quality, and financial behavior positively and significantly affect beneficiary families' welfare.